State of the art of the migration research in Poland - Anna Kicinger; Agnieszka Weinar (University of Warsaw, Centre of Migration Research (CMR), 2007)
The aim of this study is to present the state of the art of the migration research in Poland after 1989. It provides for the overview of the development of migration research according to various fields of migration studies that developed in Poland. The study covers over 300 works on contemporary migratory phenomena published by Polish scientists after 1989. It begins with an overview of migratory movements in Poland in 20th century presented along to the European migratory history. This presentation is followed by introductory reflections on the rebirth of migration research in Poland after 1989. Then, the analysis of studies of emigration from Poland come in first place, encompassing also separate sections on the research on Polish diaspora abroad after 1989. Research on the immigration to Poland and the development of migrant communities in the country is presented in the following chapter. Furthermore, the study provides for the overview of the research on migration policy and law. Last but not least, the studies on the demography and statistics of international migration are briefly explained and highlighted. A separate chapter is devoted to the methodological background of the migration research in Poland. The study ends with the conclusions that summarize the most important scientific achievements of Polish researchers in the field of migration research after 1989.
Keywords: 330; Internationale Migration; Forschung; Polen